Government R&D subsidies and the manipulative innovation strategy of Chinese renewable energy firms. Issue 2 (10th July 2023) - Ying, Qianwei; Yang, Shanye; He, Siyi
Abstract: Renewable energy technology innovation is the key to alleviating environmental issues. The Chinese government promotes corporate innovation in the renewable energy industry by providing R&D subsidies. This paper investigates the impact of R&D subsidies on innovation strategies in Chinese renewable energy listed firms from 2008 to 2017. The results show that R&D subsidies induce firms to adopt a manipulative innovation strategy that increases innovation quantity but reduces innovation quality, especially in regions with low marketization or unfair competition. We further find that the choice of manipulative innovation strategy is caused by the flawed subsidy distribution system and examination procedures of subsidy use. This paper deepens the understanding of the relationship between government subsidies and corporate innovation strategy and provides new enlightenments for emerging economies to enhance the effectiveness of subsidy policies.